Map Production from Google Earth Snapshot - Elnaggar, Aly Mohamed; Hosny, Mohamed; Elhabrouk, Hosam; Abdel wakeel, Sameh (IJRDO-Journal of Applied Science, 2019)
The ubiquitous Google Earth service is arguably the most popular and the most commonly used internet service that offers a free access to the global collection of satellite and aerial imagery. It provides an easy access to cost free image data collected from several sources which aims to produce maps benefit the community. This contemporary high-resolution archive of the Earth’s landmass represents a rapidly expanding, significant and largely unexploited resource for scientific inquiry. Therefore, many individuals and researchers still use Google Earth as a reliable and accurate data source for mapping applications. This issue raises questions about the expected positional accuracy of Google Earth and the impact of height of the scene on the planimetric accuracy, which is the main interest of the current research. In this context, the positional accuracy assessment was not carried out directly on the Google Earth imagery, but on a selected scene for a certain study area that resulted in a corresponding non georeferenced image. Then, it is georeferenced with the aid of some control points in order to be compared with a base ground-surveying map, on which the accuracy assessment will depend on the coordinates’ discrepancies of some selected well-defined check points. The results have a significant accuracy to derive planimetric maps of different scale.